2018
DOI: 10.1136/bmjopen-2018-023137
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and accuracy of delirium assessments among investigators at multiple international centres

Abstract: IntroductionDelirium is a common, serious postoperative complication. For clinical studies to generate valid findings, delirium assessments must be standardised and administered accurately by independent researchers. The Confusion Assessment Method (CAM) is a widely used delirium assessment tool. The objective was to determine whether implementing a standardised CAM training protocol for researchers at multiple international sites yields reliable inter-rater assessment and accurate delirium diagnosis.MethodsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…Given time constraints, uncertainty, and changing conditions, delirium is often unrecognized in the ICU or is recognized in a delayed fashion. This difficulty is compounded by the lack of a gold standard for delirium assessment and the low reliability of delirium assessments without significant and continued training ( 46 ). The studies reviewed generally seemed to voice an appreciation for the challenge of predicting delirium amidst the high demands of the critical care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Given time constraints, uncertainty, and changing conditions, delirium is often unrecognized in the ICU or is recognized in a delayed fashion. This difficulty is compounded by the lack of a gold standard for delirium assessment and the low reliability of delirium assessments without significant and continued training ( 46 ). The studies reviewed generally seemed to voice an appreciation for the challenge of predicting delirium amidst the high demands of the critical care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Another valuable characteristic of the CAM is that it can be used for assessment of delirium severity [7, 20]. The trial by Maybrier et al [21] was an important antecedent to the current study. It demonstrated, using a different but similarly rigorous training approach, that investigators at multiple international sites, with varying levels of clinical experience, could reliably assess delirium using the CAM.…”
Section: Discussionmentioning
confidence: 99%
“…Members of our research team have previously demonstrated the value of actual patient training complemented by video education [21]. It is likely that the rigour of the training and the reliability of the instrument used (in this case the repeatedly validated CAM) are more important than the training method.…”
Section: Discussionmentioning
confidence: 99%
“…The CAM long form has been demonstrated to have excellent psychometric properties for both hypoactive and hyperactive delirium 59 . Programmatic training, coupled with the highly structured use of the CAM long form (as we are doing in the trial), has demonstrated excellent inter-rater reliability of researchers 28, 60 . In addition, by complementing the CAM long form (or CAM-ICU) with validated chart review 50 , we are bolstering delirium detection and minimizing missing primary outcome assessments.…”
Section: Data Collectionmentioning
confidence: 97%